Bohdan-Ihor Antonycz - poeta pogranicza - Ksenicz, Andrzej (Acta Polono-Ruthenica, 2006)
In this article an attempt has been made to explicate an understanding of the role of poet as an artist crossing borders of different cultures of Europe and the world. Born in the multicultural Galicia the author was able to see himself in the role of artist relating experiences of different nations and cultures. Traditions of the East and the West, Polish and Ukrainian cultures and literatures such as German, Spanish, French, and American took its place in the imagination of the poet. But it seems that the starting point for the author of Christmas was Slavic mythology, Eastern tradition and Christian philosophy.